Evaluation of a Commercial Off The Shelf CMOS Image Sensor for X-ray spectroscopy up to 24.9 keV - Pérez, M.; Sofo Haro, M.; Lipovetzky, J.; Cicuttin, A.; Crespo, M.L.; Alcade Bessia, F.; Gómez Berisso, M.; Blostein, J.J. (Elsevier, 2020)
Fil: Pérez, M. Comisión Nacional de Energía Atómica. Instituto Balseiro; Argentina; Universidad Nacional de Cuyo; Argentina